Decreased maternal behavior and anxiety in ephrin‐A5−/− mice. (22nd September 2016) - Sheleg, M.; Yu, Q.; Go, C.; Wagner, G. C.; Kusnecov, A. W.; Zhou, R.
Abstract : During development of the nervous system, molecular signals mediating cell–cell interactions play critical roles in the guidance of axonal growth and establishment of synaptic functions. The Eph family of tyrosine kinase receptors and their ephrin ligands has been shown to mediate neuronal interactions in the development of topographic axon projection maps in several brain regions, and the loss of Eph activities result in defects in select axonal pathways. However, effects of deficiencies of the Eph signals on animal behavior have not been well documented. In this study, we showed that inactivation of a ligand of the Eph receptors, ephrin‐A5, resulted in defects in maternal behavior and alterations in anxiety. Female ephrin‐A5 −/− mice show significant defects in nest building and pup retrieval. In addition, lower levels of anxiety were observed in both male and female null mice. These changes were not due to deficiencies in estradiol, progesterone or corticosterone levels. Our observations suggest that ephrin‐A5 plays a key role in the development and/or function of neural pathways mediating mouse maternal care and anxiety. Abstract : Inactivation of ephrin‐A5 reduces maternal behavior in female mice . During development of the nervous system, molecular signals mediating cell–cell interactions play critical roles in the guidance of axonal growth and establishment of synaptic functions. The Eph family of tyrosine kinase receptors and their ephrin ligands has been shown to mediate neuronal interactions in the development of topographic axon projection maps in several brain regions, and the loss of Eph activities result in defects in select axonal pathways. However, effects of deficiencies of the Eph signals on animal behavior have not been well documented. In this study, we showed that inactivation of a ligand of the Eph receptors, ephrin‐A5, resulted in defects in maternal behavior and alterations in anxiety. Female ephrin‐A5 −/− mice show significant defects in nest building and pup retrieval. In addition, lower levels of anxiety were observed in both male and female null mice. These changes were not due to deficiencies in estradiol, progesterone or corticosterone levels. Our observations suggest that ephrin‐A5 plays a key role in the development and/or function of neural pathways mediating mouse maternal care and anxiety.